Croatia E(n)d-en on Earth - Sertić, Oliver (Fade In, 2006)
Verzio FF submission In 2004 in Croatia, Law on Asylum came into force. In the next two years, 300 people asked for the asylum status in Croatia. No one has got it yet. The film follows the activities of Centre for Peace Studies in the campaign revealing why government institutions are still not willing to begin the integration of people with potential asylum status into the society.